Ammonia Volatilization from Urea-Application Influenced Germination and Early Seedling Growth of Dry Direct-Seeded Rice - Xiaoli Qi; Wei Wu; Farooq Shah; Shaobing Peng; Jianliang Huang; Kehui Cui; Hongyan Liu; Lixiao Nie (The Scientific World Journal)
Poor seed germination and early seedling growth associated with urea-induced soil ammonia volatilization are major constraints in the adoption of dry direct-seeded rice. To directly examine soil ammonia volatilization and its damage to seed germination and early seedling growth of dry direct-seeded rice when urea is applied at seeding, two Petri-dish incubation experiments and a field experiment were conducted. Ammonia volatilization due to urea application significantly reduced seed germination and early seedling growth of dry direct-seedling rice. NBPT significantly reduced ammonia volatilization following urea application. The application of ammonium sulfate, instead of urea at seeding, may mitigate poor crop establishment of dry direct-seeded rice. Root growth of dry direct-seeded rice was more seriously inhibited by soil ammonia volatilization than that of shoot. Results suggest that roots are more sensitive to soil ammonia toxicity than shoots in dry direct-seeded rice system when N is applied as urea at seeding.